Microsomal Omega-3 Fatty Acid Desaturase Genes in Low Linolenic Acid Soybean Line RG10 and Validation of Major Linolenic Acid QTL - Reinprecht, Yarmilla; Pauls, K. Peter (Frontiers in Genetics, 2016)
High levels of linolenic acid (80 g kg-1) are associated with the development of off-flavours and poor stability in soybean oil. The development of low linolenic acid lines such as RG10 (20 g kg-1 linolenic acid) can reduce these problems. The level of linolenic acid in seed oil is determined by the activities of microsomal omega-3 fatty acid desaturases (FAD3). A major linolenic acid QTL (>70 % of variation) on linkage group B2 (chromosome Gm14) was previously detected in a recombinant inbred line population from the RG10 x OX948 cross. The objectives of this study were to validate the major linolenic acid QTL in an independent population and characterize all the soybean FAD3 genes. Four FAD3 genes were sequenced and localized in RG10 and OX948 and compared to the genes in the reference Williams 82 genome. The FAD3A gene sequences mapped to the locus Glyma.14g194300 [on the chromosome Gm14 (B2)], which is syntenic to the FAD3B gene (locus Glyma.02g227200) on the chromosome Gm02 (D1b). The location of theFAD3A gene is the same as was previously determined for the fan allele, that conditions low linolenic acid content and several linolenic acid QTL, including Linolen 3-3, mapped previously with the RG10 x OX948 population and confirmed in the PI 361088B x OX948 population as Linolen-PO(FAD3A). The FAD3B gene-based marker, developed previously, was mapped to the chromosome Gm02 (D1b) in a region containing a newly detected linolenic acid QTL [Linolen-RO(FAD3B)] in the RG10 x OX948 genetic map and corresponds well with the in silico position of the FAD3B gene sequences. FAD3C and FAD3D gene sequences, mapped to syntenic regions on chromosomes Gm18 (locus Glyma.18g062000) and Gm11 (locus Glyma.11g227200), respectively. Association of linolenic acid QTL with the desaturase genes FAD3A and FAD3B, their validation in an independent population, and development of FAD3 gene-specific markers should simplify and accelerate breeding for low linolenic acid soybean cultivars.